2010
DOI: 10.1038/jhg.2010.133
|View full text |Cite
|
Sign up to set email alerts
|

Association of serotonin transporter gene variation with smoking, chronic obstructive pulmonary disease, and its depressive symptoms

Abstract: A serotonin transporter gene, SLC6A4, is thought to be related to nicotine dependence and depression, one of the comorbidities of chronic obstructive pulmonary disease (COPD). To investigate the association between SLC6A4 variation and tobacco consumption, susceptibility to COPD, and depression status. In all, 247 patients with COPD and 119 control subjects were genotyped for 5 tag single-nucleotide polymorphisms (SNPs) of SLC6A4. We analyzed the correlation between these genotypes and COPD, using the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…In a study of 185 current smokers, Lerman et al (2000) observed a positive association between neuroticism and smoking behaviors in individuals with S expression of the 5-HTTLPR region, but not those with the L genotype. These findings were supported by Ishii et al (2011), who found that 5-HTTLPR S genotype expression was associated with 247 patients with chronic obstructive pulmonary disease (COPD). These results are encouraging, though there are also conflicting results.…”
Section: Molecular Genetics Of Smoking and Depressionsupporting
confidence: 60%
See 1 more Smart Citation
“…In a study of 185 current smokers, Lerman et al (2000) observed a positive association between neuroticism and smoking behaviors in individuals with S expression of the 5-HTTLPR region, but not those with the L genotype. These findings were supported by Ishii et al (2011), who found that 5-HTTLPR S genotype expression was associated with 247 patients with chronic obstructive pulmonary disease (COPD). These results are encouraging, though there are also conflicting results.…”
Section: Molecular Genetics Of Smoking and Depressionsupporting
confidence: 60%
“…Positive findings in both association (e.g., Audrain-McGovern et al 2004: Ishii et al 2011Stapleton et al 2011) and genetic linkage (Pergadia et al 2011) studies, however, are providing a promising foundation for future investigations.…”
Section: Molecular Genetics Of Smoking and Depressionmentioning
confidence: 91%
“…The impacts of CS exposure on nocturnal activity are particularly profound and suggest the development of a “depression-like” behavioral pattern in these mice [39]. It has been shown that altered rhythms of plasma 5HT, CORT, and cortisol levels and genetic polymorphisms of the clock genes and 5HT-receptors are directly associated with depression, sleep disorders and decreased locomotor activity [23], [38], [46], [49], [61], [62]. Moreover, it has been reported that plasma levels of 5HT and CORT are elevated by CS exposure in mice [63], [64], presumably due to increased systemic oxidative and carbonyl stress [65].…”
Section: Discussionmentioning
confidence: 99%
“…The genetic basis for fatigue, 6,58-60 pain, 18,19,61-64 depression, 11,12,65-67 and sleep disturbance 7-9,68 in patients with cancer and other chronic medical condition has been the subject of a number of recent reviews. Again, many of the genetic studies of these symptoms in cancer patients have focused on an evaluation of candidate genes associated with pro- and anti-inflammatory cytokines.…”
Section: Studies Of Genomic Biomarkers For Common Cancer Symptomsmentioning
confidence: 99%